Sheikh Muhammad Al-Khal’s attempts in the field of Kurdish literature - Wali, Asst. L. Nechirwan Jassim (Sulaimani Journal for Humanities, 2023)
This book titled (Sheikh Muhammad Al-Khal’s attempts in the field of Kurdish literature) consists of an introduction, two sections, and a list of sources. The first section, titled (Investigation of Poetry and the Literary Essay), consists of two axes. In the first axis, the researcher tried to explain the role of Sheikh Muhammad Al-Khal in investigating the lives and poetry of Kurdish poets. The researcher devoted the second axis to shed light on the role of Sheikh Al-Khal in writing and publishing Kurdish literary articles. The second section is devoted to oral literature and folklore and consists of two axes. In the first axis of the second section, the researcher tried to know proverbs and sayings and mentioned some Kurdish proverbs and aphorisms. In the last axis, the researcher tried to search for humorous literature and mentioned some Kurdish humorous stories and showed the most prominent features of humorous literature according to his perception. At the end of the research, we published the most important results that we obtained during this research.
Keywords: Sheikh Muhammad AlKhal; Kurdish literature; folkloric literature